Effect of protein, carbohydrate, lipid, and selenium levels on the performance, carcass yield, and blood changes in broilers - Hada, Fh [UNESP]; Malheiros, Rd; Silva, Jdt; Marques, Rh [UNESP]; Gravena, Ra [UNESP]; Silva, Vk [UNESP]; Moraes, Vmb [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2013)
The objective of this study was to evaluate the performance, carcass and parts yield, and blood changes in broilers fed different protein, carbohydrate, and lipid levels. Birds were fed a commercial diet until seven days of age. On day 8, birds were distributed according to a completely randomized experimental design in a 4 x 2 factorial arrangement (control diet, low protein diet, low carbohydrate diet or low lipid diet vs. supplementation of 0 or 0.3ppm organic selenium) with four replicates of 15 birds each. Broilers fed low protein presented lower body weight, feed intake, and worse feed conversion ratio on day 42, as well as lower carcass and breast yields, higher leg and abdominal fat yields, higher triglyceride and lower uric acid blood levels. Broilers fed the low carbohydrate diets presented low glucose levels on days 14 and 42.Creatine-kinase (CK) levels increased as birds aged. The livability of broilers fed the low protein diets improved and of those fed low carbohydrate diets worsened with dietary selenium addition on days 35 and 42. Selenium supplementation increased glucose levels in 42-d-old broilers. Changes in dietary protein caused more impact on broiler performance compared with carbohydrates and lipids. Changes in macronutrients caused metabolic changes in broilers. Selenium affected broiler livability as measured on days 35 and 42, and glucose blood levels.
Keywords: Carbohydrates; Lipids; Blood parameters; Protein; selenium